Gambaran Minat Baca Dan Kemampuan Membaca Pemahaman Siswa Kelas V SD - satriani satriani (Universitas Negeri Makassar, 2021)
The problem studied this study was the relationship between reading interest and reading comprehension ability of fifth grade students SD Gugus 1, Kecamatan Ulaweng Kabupaten Bone. The research approach is a quantitative approach. This type of research is a correlation study. The data analysis technique is descriptive statistical analysis and correlation analysis. The results showed that the reading interest of the fifth grade students of SD Gugus I, Kecamatan Ulaweng Kabupaten Bone was in the high category and the reading comprehension ability of the fifth grade students of SD Gugus I, Kecamatan Ulaweng Kabupaten Bone was in the moderate category and there was no significant relationship between reading interest and reading comprehension ability. Grade V students of SD Gugus I, Kecamatan Ulaweng Kabupaten Bone.